BAG-1 suppresses expression of the key regulatory cytokine transforming growth factor beta [TGF-β1] in colorectal tumour cells - Skeen, Victoria R. (2012)
As colorectal cancer remains the second highest cause of cancer-related deaths in much of the industrialised world, identifying novel strategies to prevent colorectal tumour development remains an important challenge. BAG-1 is a multi-functional protein, the expression of which is up-regulated at relatively early stages in colorectal tumorigenesis. Importantly, BAG-1 is thought to enhance colorectal tumour progression through promoting tumour cell survival. Here we report for the first time a novel role for BAG-1, establishing it as a suppressor of transforming growth factor beta [TGF-β1] expression in colorectal tumour cells. Microarray analysis first highlighted the possibility that BAG-1 may regulate TGF-β1 expression, a key cytokine in normal colonic tissue homeostasis. Q-RT-PCR and ELISA demonstrated TGFB1 mRNA and protein expression to be significantly increased when BAG1 levels were reduced by siRNA; additionally, induction of BAG-1L caused suppression of TGFB1 mRNA in colorectal tumour cells. Using reporter and ChIP assays, a direct association of BAG-1 with the TGFB1 gene regulatory region was identified. Immunohistochemistry and Weiser fraction data indicated levels of BAG-1 and TGF-β1 are inversely correlated in the normal colonic epithelium in vivo, consistent with a role for BAG-1-mediated repression of TGF-β1 production. In vitro studies showed that the change in TGF-β1 production following manipulation of BAG-1 is functionally relevant; through induction of anchorage-independent growth in TGF-β1 dependent NRK fibroblasts and regulation of SMAD2 phosphorylation in TGF-β1 sensitive adenoma cells. Taken together, this study identifies the anti-apoptotic protein BAG-1 as a suppressor of the inhibitory growth factor TGF-β1, suggesting that high expression of BAG-1 can impact on a number of the hallmarks of cancer, of potential importance in promoting the early stages of colorectal tumorigenesis. Establishing BAG-1 as a repressor of TGF-β1 has important biological implications, and highlights a new role for BAG-1 in colorectal tumorigenesis.